The relationship between calcium, zinc and mothers height consumption with stunting incidence in Bengkulu City in 2024 - Inge Dinda; Desri Suryani; Yunita Yunita (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Stunting is a chronic nutritional problem influenced by multiple factors, including dietary intake and maternal conditions. Low calcium and zinc intakes can hinder bone growth and metabolic processes, thereby increasing the risk of stunting. In addition, short maternal height, as a reflection of past nutritional status, played a role in fetal growth. This study aimed to analyze the association between calcium and zinc intake, maternal height, and the incidence of stunting among children in Bengkulu City. This quantitative study employed a cross-sectional design and was conducted at the Sawah Lebar Primary Health Center, Bengkulu City, from April to May 2024. A total of 77 children aged 6–59 months were selected using simple random sampling. Dietary intake data were obtained through interviews using a semi-FFQ, while nutritional status was assessed using the height-for-age index. Data were analyzed using Pearson’s correlation test. The results showed a significant association between calcium intake (r = 0.636), zinc intake (r = 0.280), and maternal height (r = 0.290) and stunting. In conclusion, the importance of adequate Ca and Zn intake and maternal nutritional status in supporting child growth. Therefore, nutritional interventions should be implemented early, not only for children but also for adolescent girls as future mothers.